a The Influence of Students’ Participation in Religious Extracurricular Activities on Religious Character at SMA Negeri 1 Pinolosian: religious extracurricular activities; student involvement; religious character; - sartika mahmud tika; Lamsike Petada; Ibnu Rawandhy N Hula (Pekerti: Journal Pendidikan Islam dan Budi Pekerti, 2025)
This study seeks to examine the effect of students’ participation in religious extracurricular activities on the development of religious character at SMA Negeri 1 Pinolosian. Employing a quantitative approach with an explanatory research design, the study aims to identify the causal relationship between the variables under investigation. The sample comprised 60 students selected through random sampling from a total population of 320 students. Data were obtained using a Likert-scale questionnaire that had undergone validity and reliability testing. The collected data were analyzed using descriptive statistical techniques and the Spearman Rank correlation test, as the data failed to satisfy the assumption of normality. The findings reveal that students’ participation in religious extracurricular activities was categorized as high, while their religious character was classified as good. Furthermore, Results of the Spearman Rank correlation test revealed a correlation coefficient of 0.892 at a significance level of 0.000, signifying a highly robust, positive, and statistically significant relationship between the intensity of students’ involvement in religious extracurricular programs and the formation of religious character. These results suggest that sustained and active engagement in school-based religious activities plays a strategic role in fostering the internalization of religious values among students. Consequently, this study contributes empirically to the development of religious extracurricular programs as an effective instrument for promoting sustainable religious character formation at the secondary education level